KEWENANGAN MAHKAMAH KONSTITUSI DALAM MENYELESAIKAN PERSELISIHAN HASIL PEMILIHAN UMUM MENURUT UU NO. 24 TAHUN 2003 TENTANG MAHKAMAH KONSTITUSI - Puspaningrum - (Universitas Slamet Riyadi, 2010)
Abstract : The Constitutional Court was established by Act No. 24 of 2003 (State Gazette number 98 of 2003). Constitutional Court as the new state institutions have a crucial role in the constitutional system of the Republic of Indonesia. The authority of the Constitutional Court provided for in Article 24 C of the 1945 Constitution. The constitution of the Constitutional Court has the four powers which shall be final, that is to test laws against the Constitution Act 1945, to decide disputes between state institutions whose authorities are granted the 1945 Constitution and an obligation that is the opinion of the Parliament to decide on alleged violations committed by the President and / or Vice President. Key Words : Constitutional Court, Authority, Elections